2023
DOI: 10.3390/ijerph20020898
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio as a Predictor of Short-Term Functional Outcomes in Acute Ischemic Stroke Patients

Abstract: Background: Neutrophil-to-lymphocyte ratio (NLR), a systemic inflammatory biomarker, has been associated with poorer outcomes in acute ischemic stroke patients. The present study was designed to expand these findings by investigating the association between NLR and short-term functional outcomes in acute ischemic stroke patients. Methods: This retrospective study evaluated patients within 7 days after the onset of acute ischemic stroke. Stroke severity on admission was measured using the National Institutes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
3
0
2
Order By: Relevance
“…The initial investigation of the relationship between the NLR and short-term mortality in stroke patients demonstrated that the NLR serves as an independent prognostic indicator of short-term mortality in AIS patients, with higher NLRs significantly associated with increased stroke-related mortality [33][34][35][36]. Min-Su Kim et al discovered a similar finding, indicating an optimal NLR threshold value of 2.09 [37]. Our study also provided evidence that the NLR is an independent factor for 3-month clinical functional outcomes in patients with AIS.…”
Section: Discussionmentioning
confidence: 93%
“…The initial investigation of the relationship between the NLR and short-term mortality in stroke patients demonstrated that the NLR serves as an independent prognostic indicator of short-term mortality in AIS patients, with higher NLRs significantly associated with increased stroke-related mortality [33][34][35][36]. Min-Su Kim et al discovered a similar finding, indicating an optimal NLR threshold value of 2.09 [37]. Our study also provided evidence that the NLR is an independent factor for 3-month clinical functional outcomes in patients with AIS.…”
Section: Discussionmentioning
confidence: 93%
“… 21 Kim et al found that the higher the NLR, the worse the short-term functional prognosis of AIS patients. 22 In addition, a study of 346 patients with AIS showed that the higher the NLR, the higher the incidence of adverse outcomes at discharge. 23 We included 861 AIS patients, and our findings suggested that the NLR was an independent risk factor for poor functional outcome at discharge, which was consistent with previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…İnmenin başlamasından sonra, periferik kanda nötrofil sayısı kısa sürede artmaktadır (26). Yüksek NLO düzeyleri inme şiddeti, kısa dönemli ölüm oranı, kısa dönemli olumsuz fonksiyonel sonuçlar ve artmış tekrarlayan iskemik inme riski ile ilişkilendirilmiştir (7). Akut iskemik inmeli hastalarda kısa dönemli fonksiyonel sonuçların NLO ile ilişkisinin incelendiği bir çalışmada, NLO düzeyi yüksek olanlarda daha yüksek USİS ile daha düşük Barthel indeksi ve kısa minimental durum muayenesi puanları elde edilmiştir (7)…”
Section: Discussionunclassified
“…Hematolojik parametrelerin inme hastalarında ilk üç aylık klinik sonuçlar ile ilişkisine daha önce bakılmıştır (6) ancak hastanede yatış sırasındaki kısa süreli klinik sonuçlar ile ilişkisine ait çalışma sayısı azdır (7). Akut iskemik inmeli hastaların yaklaşık üçte biri erken nörolojik kötüleşme yaşamaktadır (8).…”
unclassified